DESIGN AND DEVELOPMENT OF 2D ANIMATION VIDEO AS A GENETIC MATERIAL BIOLOGY LEARNING MEDIA USING ADDIE METHOD - Deli Deli; Widya Risma Ilahi (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Genetic material is one of the lessons that is abstract, so that abstract material becomes easier to understand, a learning media that applies animation is needed. The use of animation in the design of this video makes the media more creative to attract students' attention, the use of animation media can also generate interest and increase student learning motivation. In addition, animated videos can also specifically explain abstract material to help students understand biology, especially genetic material. This study uses the ADDIE method which has five stages, namely Analysis, Design, Development, Implementation, Evaluation, and is designed using Adobe After Effects software. The results of the design and development of animated videos that have been carried out by the author will be implemented on youtube. Thus, the use of animated media is easy to find and can help students in studying the biology of genetic material.